VLBI and GPS carrier phase time and frequency transfer - Takiguchi, H; Koyama, Y; Ichikawa, R; Gotoh, T; Ishii, A; Hobiger, T (National Institute of Information and Communications Technology (NICT), 2010)
As one of the new frequency transfer technique to compare the next highly stable frequency standards, we proposed the geodetic VLBI technique. We evaluated the ability of VLBI frequency transfer by comparison with GPS carrier phase frequency transfer. These comparisons showed that geodetic VLBI technique has the potential for precise frequency transfer. In this paper, we describer the previous comparison with VLBI and GPS carrier phase.
Keywords: Very Long Baseline Interferometry; Global Positioning System; Time and frequency transfer